PENERAPAN METODE TALKIN DALAM MENINGKATKAN MOTIVASI BELAJAR AL-QUR'AN PADA ANAK DAN REMAJA DI LINGKUNGAN MASJID (STUDI KASUS DI TPQ MASJID ABU BAKAR, JL. SEMANGKA, PADANG SERAI, KECAMATAN KAMPUNG MELAYU, KOTA BENGKULU, PROVINSI BENGKULU) - Chandra, Pasmah; Retno Wulansari, Dwi; Zulaikah, Siti; Revano Danendra, Aldo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the application of the Talkin method in enhancing Qur'anic learning motivation among children and adolescents at the Taman Pendidikan Al-Qur'an (TPQ) of Abu Bakar Mosque, located at Jl. Semangka, Padang Serai, Kampung Melayu District, Bengkulu City, Bengkulu Province. The Talkin method — a classical Islamic pedagogical approach grounded in oral transmission (talaqqi musyafahah) — is analyzed through its motivational impact on learners aged 5–17. Using a descriptive-qualitative approach with data collected through participatory observation, in-depth interviews, documentation, and Focus Group Discussion (FGD), this study finds that the Talkin method significantly increases intrinsic and extrinsic motivation, as evidenced by improved attendance rates (from 68% to 91%), greater enthusiasm for recitation practice, and measurable progress in reading proficiency across all assessed dimensions. Motivational gains are attributed to four key mechanisms: direct emotional bonding between teacher and learner, immediate corrective feedback, the cultivation of a sense of spiritual progression, and consistent positive reinforcement. Challenges include a non-optimal teacher-to-student ratio and the need for parental involvement. The study recommends targeted recruitment of qualified instructors and integration of gamified progress-tracking systems to sustain long-term motivation.